Side-group-induced polymorphism in self-assembled monolayers: 3,5-Bis(trifluoromethyl)benzenethiolate films on Au(111) - Bashir, Asif; Sauter, Eric; Zharnikov, Michael (ChemPhysChem, 2017)
The structure and molecular organization of self-assembled monolayers (SAMs) depend on a complex interplay of intermolecular and molecule-substrate interactions, so that even a small change in molecular composition can result in noticeable changes in the SAM structure. Herein we show that decoration of the most basic aromatic SAM constituent, benzenethiol, with two trifluoromethyl groups leads to distinct polymorphism in the respective SAMs, in which the appearance of a specific structural phase or a combination of several different phases is dependent on the parameters of the preparation procedure. High-quality films with a single crystallographic phase and significantly large domains could only be prepared after a short immersion time (5 min) and an additional re-immersion of the sample in pure ethanol at an elevated temperature. A standard 24 h immersion at room temperature led to poorly defined films with a large defect density and only a small portion of the surface covered by well-ordered molecular domains.